Epidemiology and molecular genotyping of echinostome metacercariae in Filopaludina snails in Lamphun Province, Thailand - Noikong W. (2014)
Objective: To analyze the prevalence of echinostome metacercariae in. Filopaludina dorliaris (F. dorliaris) and Filopaludina martensi martensi (F. martensi martensi) and genotype variation of echinostome metacercariae by using random amplified polymorphic DNA (RAPD) analysis. Methods: Filopaludina sp. snails were collected from eight localities of Lamphun Province, Northern Thailand and examined for echinostome metacercariae. RAPD-PCR was used to analyze genotype variation of echinostome metacercariae. Results: A total of 3 226 F. dorliaris and F. martensi martensi snails were collected from eight localities. The overall prevalences of echinostome metacercariae in F. dorliaris and F. martensi martensi were 40.89% and 36.27%, while the intensity of infection was 20.37 and 12.04, respectively. The dendrogram constructed base on RAPD profiles, 4 well supported domains were generated; (i) group of metacercariae from Ban Hong, Mae Ta, Meaung, Pa Sang, Toong Hua Chang, and Weang Nong that were clustered in the group of E. revolutum, (ii) Ban Thi, (iii) Lee, and (iv) 3 adults of an out group. Conclusions: This research demonstrated RAPD profiling has been a useful tool to detect DNA polymorphisms to determine genetic relationship between echinostome metacercariae in Lamphun Province, Northern Thailand. © 2014 Hainan Medical College.